2013
DOI: 10.1501/tarimbil_0000001247
|View full text |Cite
|
Sign up to set email alerts
|

Seed size and shape analysis of registered common bean (Phaseolus vulgaris L.) cultivars in Turkey using digital photography

Abstract: In this study, the size and shape properties of twelve different bean cultivars (eleven varieties and a genotype) were determined using image processing method on digital photography and the cultivars were grouped depending on their properties. The highest mean values of geometric diameter, projected area, length, width and shape factor in the study were determined in the 'Çayırlı' genotype. 'Terzibaba' cultivar, more spherical shape at width orientation compared to other cultivars, had the lowest value of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 21 publications
0
1
0
2
Order By: Relevance
“…The minimum and maximum values ranged between 8.06 and 19.98 mm for L, 4.24 and 9.56 mm for T, and 5.06 and 12.63 mm for W. For characteristic 100 seed weight the mean value of all 953 accessions was 51.13 ± 13.84 g, while the minimum and maximum values ranged between 19.32 and 98.39 g. The highest coefficient of variation was calculated for the 100 seed weight (27.06%) and the lowest for W/T (12.64%). As discussed by Rana et al [22] for 4274 common bean accessions conserved in Indian gene bank, L ranged 5.0–20.3 mm, W 2.0–12.0 mm and 100 seed weight 3.5–96.3 g. Similarly, Kara et al [23] reported for 12 registered Turkish common bean genotypes L 9.1–17.8 mm, W 5.8–10.0 mm, T 4.6–6.0 mm and 100 seed weight 18.0–65.6 g. As discussed by Giurcă [24] for 9 common beans originating from northern Romania and western Ukraine, L ranged 11.8–18.0 mm, W 7.4–9.7 mm, T 4.4–6.9 mm and 100 seed weight 34.3–54.2 g. Logozzo et al [4] evaluated 533 accessions of the European common bean germplasm and reported accessions with L 12.0–13.9 mm (35.5%), W 7.1–8.0 mm (33.0%) and T 5.0–5.9 mm (37.1%) were the most frequent.…”
Section: Resultsmentioning
confidence: 92%
“…The minimum and maximum values ranged between 8.06 and 19.98 mm for L, 4.24 and 9.56 mm for T, and 5.06 and 12.63 mm for W. For characteristic 100 seed weight the mean value of all 953 accessions was 51.13 ± 13.84 g, while the minimum and maximum values ranged between 19.32 and 98.39 g. The highest coefficient of variation was calculated for the 100 seed weight (27.06%) and the lowest for W/T (12.64%). As discussed by Rana et al [22] for 4274 common bean accessions conserved in Indian gene bank, L ranged 5.0–20.3 mm, W 2.0–12.0 mm and 100 seed weight 3.5–96.3 g. Similarly, Kara et al [23] reported for 12 registered Turkish common bean genotypes L 9.1–17.8 mm, W 5.8–10.0 mm, T 4.6–6.0 mm and 100 seed weight 18.0–65.6 g. As discussed by Giurcă [24] for 9 common beans originating from northern Romania and western Ukraine, L ranged 11.8–18.0 mm, W 7.4–9.7 mm, T 4.4–6.9 mm and 100 seed weight 34.3–54.2 g. Logozzo et al [4] evaluated 533 accessions of the European common bean germplasm and reported accessions with L 12.0–13.9 mm (35.5%), W 7.1–8.0 mm (33.0%) and T 5.0–5.9 mm (37.1%) were the most frequent.…”
Section: Resultsmentioning
confidence: 92%
“…The minimum and maximum values ranged between 10.01 and 19.5 mm for L, and 6.07 and 12.95 mm for W. For characteristic1,000 seed weight the mean value of all 28 accessions was 521.34 ± 208.19 g, while the minimum and maximum values ranged between 136.96 and 1,045 g. The highest coefficient of variation was calculated for the 1,000 seed weight (39.9%) and the lowest for L/W (13.2%). As discussed by Rana et al [20] for 4,274 common bean accessions conserved in Indian gene bank, L ranged 5.0 -20.3 mm, W 2.0 -12.0 mm and 100 seed weight 3.5 -96.3 g. Similarly, Kara et al [21] reported for 12 registered Turkish common bean accessions genotypes L 9.1 -17.8 mm, W 5.8 -10.0 mm, T (seed thickness) 4.6 -6.0 mm and 100 seed weight 18.0 -65.6 g. As discussed by Giurcă [22] for 9 common beans accessions originating from northern Romania and western Ukraine, L ranged 11.8 -18.0 mm, W 7.4 -9.7 mm, T (seed thickness) 4.4 -6.9 mm and 100 seed weight 34.3 -54.2 g. Logozzo et al [23] evaluated 533 accessions of the European common bean germplasm and reported accessions with L 12.0 -13.9 mm (35.5%), W 7.1 -8.0 mm (33.0%) and T 5.0 -5.9 mm (37.1%) were the most frequent. As discussed by Sinkovič et al [16] for 953 common bean accessions conserved in Slovene gene bank at the Agricultural Institute of Slovenia, being part of the National plant gene bank, L (range 7.3 -27.2 mm); T (range 4.2 -11.0 mm); W (range 0.3 -16.5 mm); L/W (range 0.4 -2.6 mm); W/T (range 0.6 -2.2 mm); and 100 for common (range 19.3 -98.4 mm) bean seed weight.…”
Section: Seed Characterization Of Common Bean Accessions (Phaseolus V...mentioning
confidence: 83%
“…Foram selecionados seis descritores de textura sendo T3, T7, T11, T15, T19 e T25, ou seja, dos 27 descritores analisadas 21 (77,77%), eram redundantes (Tabela 3). 0,00 0,00 100,00 22 0,00 0,00 100,00 23 0,00 0,00 100,00 24 0,00 0,00 100,00 25 0,00 0,00 100,00 26 0,00 0,00 100,00 27 0,00 0,00 100,00 Kara et al (2013), utilizaram as propriedades de tamanho e forma de sementes que foram determinadas usando o método de processamento de imagem em fotografia digital para agrupar 12 variedades de feijão na Turquia. Os autores também verificaram que os dois primeiros componentes explicaram 96,1% da variação total, com a formação de quatro grupos.…”
Section: Resultsunclassified
“…Assim, características que nunca foram mensuradas antes ou somente em situações específicas estão começando a ser medidas com maior frequência e de maneira fácil como as características relacionadas ao tamanho, cor, forma e textura da semente (FIORANI; SCHURR, 2013). A análise digital de imagem de sementes vem sendo utilizada para a identificação de cultivares, determinação de sementes de diferentes cores, danos mecânicos e de classificação de diferentes tamanhos de sementes (VENORA et al, 2009;KARA et al, 2013;PINTO et al, 2015;ANDRADE et al, 2016).…”
Section: Introductionunclassified